A photocurable method for copper(ii) oxide-doped polyaniline conducting polymer membrane synthesis - Illyas Md Isa (Tanjung Malim, 2023)
A photocurable method for copper(ii) oxide-doped polyaniline conducting polymer membrane synthesis by Illyas Md Isa